On the use of silicon photomultipliers for thermoluminescence measurements. (May 2021) - Kim, Hyoungtaek; Lim, Kyung Taek; Lee, Jungil; Cho, Gyuseong
Abstract : Abstract: In this work, we evaluate the use of silicon photomultipliers (SiPMs) as a suitable candidate for use as a photodetector for thermoluminescence measurements. The measurements were based on the Hamamatsu S13360-series with a pixel area of 3 × 3 mm 2 and microcell pitches of 25 μm, 50 μm, and 75 μm, which were mounted on a Risø TL/OSL reader system with LiF:Mg, Cu, Si chosen as the reference TL material. Through the experiment, we showed that the typical TL glow curves can be obtained with SiPMs, despite their lower geometric efficiencies. We also demonstrated the dose response of SiPMs ranging from 6 to 66 mGy for three different photon threshold levels. The detection limit was approximately equal to 0.2 mSv, 0.08 mSv, and 0.17 mSv for 25 μm, 50 μm, and 75 μm SiPMs, respectively. More importantly, a sensitivity change and sensor temperature depending on a TL reading up to 260 °C was monitored on a sequential readout. Lastly, we discuss some of the possible benefits and limitations of SiPM-based TL measurements in comparison to PMT-based TL measurements. Highlights: Glow curve of LiF:Mg, Cu, Si was measured by a SiPM based TL reader system. Feasibility of SiPMs for replacing PMTs in TL measurements was confirmed. A temperature correction technique is required for SiPMs to obtain stable TL signals.